Pendampingan Sistem Perekaman Data Pasien pada Klinik Pratama Kebongembong Kecamatan Pagerruyung Kabupaten Kendal, Jawa Tengah - Rozaq Isnaini Nugraha; Supriyanto Supriyanto; Sigit Sugiharto (Lembaga Pengembangan Kinerja Dosen, 2024)
A medical record is a file that contains document records regarding the patient's identity, examination, treatment, actions, and other services that have been provided to the patient. Pratama Clinic as a health service provider must have a competitive advantage and be competitive in terms of the quality of the health services provided. Pratama Halyna Clinic is located in Gajahan, Kebongembong, Kec. Pagerruyung, Kendal Regency, Central Java. In this clinic, there are several polyclinics, namely, general, Kia / birth control, elderly, childbirth, and circumcision. To carry out data recapitulation to find out the number of patients who visited and the polyclinics that were frequently visited, the operator carried out manual calculations, namely by opening the data in the form of paper regarding patient recaps for that month which was then carried out by manual counting. Based on these observations and observations, we, the staff, propose creating a patient data recording system.